MODELO CONCEITUAL TEÓRICO SOBRE PERCEPÇÃO COGNITIVA DO AMBIENTE CONSTRUÍDO - Faganello, Adriana; Iarozinski Neto, Alfredo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article aimed to investigate the processes by which the individual appropriates the environment through cognitive perception and reveals itself through his behavior. The result was the construction of a theoretical conceptual model on the cognitive perception of the environment built based on the epistemology of the theory of autopoiesis, which comprises three main assumptions: Ontogeny / Natural Derivative, the historical construction of the subject's life; Conduct being the action of the individual in the middle and the Structural Coupling, the set of changes that the medium causes in the structure of a given individual and vice versa, in a circular relation. In the model, direct and indirect influences form an autopoietic system. It is important to build knowledge about the concepts of cognitive perception of the environment built for the APO, and from this review the method of designing architectural projects.